Size-Fractionated Microbiome Structure in Subarctic Rivers and a Coastal Plume Across DOC and Salinity Gradients - Blais, Marie-Amélie; Matveev, Alex; Lovejoy, Connie; Vincent, Warwick F. (Frontiers in Microbiology, 2022)
Little is known about the microbial diversity of rivers that flow across the changing subarctic landscape. Using amplicon sequencing (rRNA and rRNA genes) combined with HPLC pigment analysis and physicochemical measurements, we investigated the diversity of two size fractions of planktonic Bacteria, Archaea and microbial eukaryotes along environmental gradients in the Great Whale River (GWR), Canada. This large subarctic river drains an extensive watershed that includes areas of thawing permafrost, and discharges into southeastern Hudson Bay as an extensive plume that gradually mixes with the coastal marine waters. The microbial communities differed by size-fraction (separated with a 3-µm filter), and clustered into three distinct environmental groups: 1) the GWR sites throughout a 150-km sampling transect; 2) the GWR plume in Hudson Bay; and 3) small rivers that flow through degraded permafrost landscapes. There was a downstream increase in taxonomic richness along the GWR, suggesting that sub-catchment inputs influence microbial community structure in the absence of sharp environmental gradients. Microbial community structure shifted across the salinity gradient within the plume, with changes in taxonomic composition and diversity. Rivers flowing through degraded permafrost had distinct physicochemical and microbiome characteristics, with allochthonous dissolved organic carbon explaining part of the variation in community structure. Finally, our analyses of the core microbiome indicated that while a substantial part of all communities consisted of generalists, most taxa had a more limited environmental range and may therefore be sensitive to ongoing change.